The Determinants on the Malaysia Total Manufactured Trade with ASEAN -5 - Yong, Teck Liang (Universiti Malaysia Sarawak (UNIMAS), 2014)
The main objective of this study is examine the determinants (Gross Domestic Product (GDP), income per capita (GDP per capita), remoteness, difference in GDP per capita and ASEAN Free Trade Area (AFTA) on Malaysia total manufactured trade with the ASEAN – 5 members. Besides, this study is adopting the annual data from 1965 to 2012. To examine the stationary of the variable in this study by using the Augmented Dickey- Fuller (ADF) test and the Philips and Perron (PP) test. Furthermore, the bounds tests and the Error Correction Model (ECM) based on the ARDL model used in this study is to find out whether there are long run relationship between the variables. The result showed there is long run relationship between the determinants. Besides, there are inconsistent of result on the relationship between the determinants and the Malaysia total manufactured trade with the ASEAN – 5 among the four type of model.